2022
DOI: 10.1186/s13568-022-01364-3
|View full text |Cite
|
Sign up to set email alerts
|

Antifouling coating based on biopolymers (PCL/ PLA) and bioactive extract from the sea cucumber Stichopus herrmanni

Abstract: An important challenge to decrease the toxic effects of the common biocides in marine environments and to achieve suitable ecofriendly natural antifouling coatings is to find effective natural antifoulants and efficient biodegradable coatings. In this study, antifouling activities of nine bioactive extracts (non-polar to polar) from different organs of the sea cucumber Stichopus herrmanni were tested against five bacterial strains, barnacle and brine shrimp larvae. The ethyl acetate extract of the body wall sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 55 publications
0
5
0
Order By: Relevance
“…Solutions of 0.5% and 1% ( w / v ) of β-CS and its three derivatives were immobilized onto poly (lactic acid) (PLA) films (Goodfellow, Cambridge, UK) through dip coating. PLA was the substrate chosen because it has been used in eco-friendly antifouling strategies, including the production of marine coatings [ 29 , 30 , 31 ]. First, to improve the CS adhesion to the surfaces, PLA films were submitted to plasma oxygen treatment (Harrick Plasma, Ithaca, NY, USA) for 15 min [ 81 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Solutions of 0.5% and 1% ( w / v ) of β-CS and its three derivatives were immobilized onto poly (lactic acid) (PLA) films (Goodfellow, Cambridge, UK) through dip coating. PLA was the substrate chosen because it has been used in eco-friendly antifouling strategies, including the production of marine coatings [ 29 , 30 , 31 ]. First, to improve the CS adhesion to the surfaces, PLA films were submitted to plasma oxygen treatment (Harrick Plasma, Ithaca, NY, USA) for 15 min [ 81 ].…”
Section: Methodsmentioning
confidence: 99%
“…C. marina DSMZ 4741 is a ubiquitous bacterium isolated from coastal seawater [ 27 ] and was chosen as a microfouler model [ 28 ]. Considering the goal of developing antifouling paints for ship hulls, PLA was the substrate chosen for this proof of concept since it has been used in several environmental-friendly antifouling approaches, including the production of marine coatings [ 29 , 30 , 31 ]. Furthermore, it is described that PLA does not biodegrade in normal ambient conditions or marine environments, and offers mechanical stability, with no changes in mechanical properties after submersion tests in the sea [ 32 ].…”
Section: Introductionmentioning
confidence: 99%
“…Benthic invertebrates in the ocean, such as sea cucumbers, sea squirts and sponges, can defend against external threats by secreting antifouling active substances. Darya et al [ 34 ] tested the antifouling activity of nine bioactive extracts (non-polar to polar) from different organs of sea cucumbers against five bacterial strains, barnacles and brine shrimp larvae and demonstrated that body wall ethyl acetate extracts had the highest in vitro antifouling activity, including the results of a 3-month live sea pegboard test that showed that antifouling coatings supplemented with body wall ethyl acetate effectively inhibited the adhesion of fouling organisms, while a combination of 80 wt.% polycaprolactones (PCL) and 20 wt.% polylactic acid (PLA) with body wall ethyl acetate exhibited the highest antifouling activity. Levert et al [ 35 ] studied five monoterpenoids (Cordiachromene A, Didehydroconicol, Epiconicol, Methoxyconidiol, Conidione) (the chemical molecular structure is shown in Figure 8 ) from secondary metabolites of sea squirts and the antifouling test results showed that Cordiachromene A and Epiconicol showed the strongest inhibitory effect on barnacle sedimentation and bacterial growth.…”
Section: New Environmentally Friendly Antifouling Coatingmentioning
confidence: 99%
“…They are lesser known, however, for their potential biofouling mitigative properties. Nearly all studies involving sea cucumbers and biofouling control have focused on using bioactive compounds from their tissues and extracts as novel antifouling coatings [24][25][26]. However, many sea cucumber species have large peltate feeding tentacles that brush the surface of soft and hard substrates, picking up organic-rich material for ingestion.…”
Section: Introductionmentioning
confidence: 99%